Immersive analytics: Building virtual data worlds for collaborative decision support - Hackathorn, Richard; Margolis, Todd (IA : 2016 Workshop on Immersive Analytics : 20 March 2016, 2016)
Immersive analytics is an emerging research area that blends analytical reasoning with immersive virtual space to enhance collaborative decision support. The intent of this position paper is to stimulate discussion and cooperation toward maturing immersive analytics. An open innovation community to build immersive data worlds has been established at ImmersiveAnalytics.com, to serve as a bridge and catalyst between academia and corporate communities. The paper outlines the objectives for analytical reasoning and immersive data spaces, followed by suggestions for the design and architecture of data worlds. Finally, current work for building data worlds is described.